Litogeoquímica correlational analysis and characterization of the Barroso Toquepala and volcanic in southern Peru - Rivera, Hugo (2012)
The constituents of Toquepala and Barroso Groups in southern Peru, according to its composition of major, minor and trace and graphing various geochemical diagrams volcanic rocks show that both groups have a degree of evolution by fractional crystallization, are the series of high-K calc-alkaline, subalkaline and nature. The contents of Sr and Rb indicate a strong assimilation and differentiation of magmas. The enrichment of LILE (<100) and a depletion of elements smaller than 10 elements HFSE negative anomalies of Nb and positive anomalies of Th, Ce, indicate that both groups are related to volcanic tectonic setting of subduction. The chemical contents of Toquepala Group are due to contamination during crustal thickening during the Cretaceous. Volcanic Group of Toquepala are peraluminous nature, and shows a differentiation that mostly covers the area of ​​rhyolite, dacite / andesite to traquidacita and basaltic andesite. The rocks are metaluminous Barroso Group, shows a higher degree of oxidation (total Fe) and varies lithologically trachyandesites / andesite, dacite / traquidacita, rhyolite and basalt / basaltic andesite trachyandesites.